7.4L: Late‐News Paper: A Thinner Phosphor Layer Fabrication Process for AC PDPs. Issue 1 (1st July 2013) - Mikami, Tomohisa; Urieu, Eiichi; Ninomiya, Syouzou; Oohata, Hisayo; Murai, Ryuichi
Abstract: SUPER Hi‐VISION PDPs. (SHV‐PDPs) have smaller volume discharge cells, which result in lower discharge efficiency. We have developed a technique for making thinner phosphor layers in PDP discharge cells, using printing technology that can provide a phosphor layer that is only 3 micrometers thick.